Standardization of Vaalai Rasa Mezhugu (VRM): A Siddha Formulation - Ramasamy, Suresh; Gopalan, Senthamil Selvi; Antonyraj, Kiruba Annammal Paul Abraham; Annamalai, Siva; Balasubramani, Abarna; Mohan, Natarajan; Subramaniam, Sanjana (International Journal of Pharmaceutical Investigation, 2025)
Background The Siddha system, widely practiced in Tamil Nadu, incorporates plant, mineral and animal components in its medicinal formulations. Vaalai Rasa Mezhugu (VRM) is one such herbo-mineral preparation indicated for conditions like throbbing pain, arthritis and lymphadenitis. Objectives This study aims to standardize VRM according to the guidelines established by the Pharmacopeia Laboratory of Indian Medicine (PLIM), addressing the urgent need for modern quality control in traditional medicine. Materials and Methods A comprehensive quality control protocol was implemented, involving physico-chemical analysis, instrumental assessments such as HPTLC (High-Performance Thin-Layer Chromatography) and evaluations for heavy metals, microbial contamination, specific pathogens, pesticide residues and aflatoxins. Results The physico-chemical analysis indicated a pH of 6.25, loss on drying at 6.68% and a total ash content of 1.735%. HPTLC fingerprinting identified eleven phytocomponents at 254 nm, 17 at 366 nm and 12 at 520 nm, demonstrating a complex phytochemical profile. Importantly, VRM was found to be free from microbial contaminants, heavy metals, specific pathogens, pesticide residues and aflatoxins below quantification limits. Conclusion These findings affirm the efficacy of Vaalai Rasa Mezhugu and establish a valuable framework for quality assurance in traditional medicine, ensuring the safety and effectiveness of this herbo-mineral formulation.
Keywords: Standardization; Vaalai Rasa Mezhugu; Physico-chemical analysis; HPTLC; PLIM Guidelines; Internal Medicine